Study the Reaction Mechanism of The Production of Novel Biopolymer [Poly (3-Hydroxybutyrate) (PHB)] from the Palm Oil Seed - Mohd Khairul Nizam, Baharudin (2012)
Poly(3-hyroxybutyrate) (PHB), is a biodegradable plastic that recognized as a potential alternative to substitute conventional petrochemical-based plastic. This biodegradable plastic is derived from bacterial fermentation using various carbon sources. Since the cost of carbon substrates has been identified as the major constrain in PHB production, inexpensive and renewable carbon substrate were currently investigated as alternative to conventional sugar-based substrate. Palm oil, massive-readily edible plant oil, may be an alternative substrate to conventional carbon source for PHB production. PHB is synthesized by Alcaligenes eutrophus in a production medium containing palm oil. Highest cell-dry weight was obtained by A. eutrophus when 20 g/L of palm oil and 0.6 g/L of urea were used. Cell-dry weight increased when the addition of starter inoculum volume increased up to 10 mL. Highest cell-dry weight was obtained at 48 to 60 hour of incubation. In a cell growth kinetic study, the total cell-dry weight obtained in presence of 20 g/L palm oil was greater than 12g/L and 16 g/L. Bacteria fermentation in the presence of 0.6 g/L urea shows greater total cell-dry weight compared to fermentation system without any addition of urea. This study proved that palm oil is a feasible and excellence carbon substrate for PHB biosynthesis by A. eutrophus. In this study, the evaluation of optimum condition for PHB biosynthesis by bacterial fermentation was accomplished.